Superman vs. Muhammad Ali - O'Neil, Dennis, 1939-2020- (DC Comics, 2010)
Together, the Man of Tomorrow and the Champ are two of the mightiest warriors the Earth has ever known. Now they must face their greatest challenge yet-- each other!